3d-SPADE: Significance evaluation of spatio-temporal patterns of various temporal extents. (November 2019) - Stella, Alessandra; Quaglio, Pietro; Torre, Emiliano; Grün, Sonja
Abstract: The Spike Pattern Detection and Evaluation (SPADE) analysis is a method to find reoccurring spike patterns in parallel spike train data, and to determine their statistical significance. Here we introduce an extension of the original statistical testing procedure which explicitly accounts for the temporal duration of the patterns. The extension improves the performance in the presence of patterns with different durations, as here demonstrated by application to various synthetic data. We further introduce an implementation of SPADE in form of a sub-module of the Python library Elephant (ELEctroPHysiological ANalysis Toolkit). The code is made publicly available on GitHub, together with detailed documentation, tutorials, and the results presented here.